Utopias of otherness : nationhood and subjectivity in Portugal and Brazil - Arenas, Fernando, 1963- (University of Minnesota Press, 2003)
In Utopias of Otherness, Fernando Arenas considers Portugal and Brazil, both subject to the economic, political, and cultural forces of postmodern globalization. Arenas analyzes responses to these trends in contemporary writers including José Saramago, Caio Fernando Abreu, Maria Isabel Barreno, Vergílio Ferreira, Clarice Lispector, and Maria Gabriela Llansol, ultimately revealing how these writers have redefined the concept of nationhood.